Prenatal Exposure to General Anesthesia and Childhood Behavioral Deficit. (September 2021) - Ing, Caleb; Landau, Ruth; DeStephano, David; Miles, Caleb H.; von Ungern-Sternberg, Britta S.; Li, Guohua; Whitehouse, Andrew J. O.
Abstract : BACKGROUND: Exposure to surgery and anesthesia in early childhood has been found to be associated with an increased risk of behavioral deficits. While the US Food and Drug Administration (FDA) has warned against prenatal exposure to anesthetic drugs, little clinical evidence exists to support this recommendation. This study evaluates the association between prenatal exposure to general anesthesia due to maternal procedures during pregnancy and neuropsychological and behavioral outcome scores at age 10. METHODS: This is an observational cohort study of children born in Perth, Western Australia, with 2 generations of participants contributing data to the Raine Study. In the Raine Study, the first generation (Gen1) are mothers enrolled during pregnancy, and the second generation (Gen2) are the children born to these mothers from 1989 to 1992 with neuropsychological and behavioral tests at age 10 (n=2024). In the primary analysis, 6 neuropsychological and behavioral tests were evaluated at age 10: Raven's Colored Progressive Matrices (CPM), McCarron Assessment of Neuromuscular Development (MAND), Peabody Picture Vocabulary Test (PPVT), Symbol Digit Modality Test (SDMT) with written and oral scores, Clinical Evaluation of Language Fundamentals (CELF) with Expressive, Receptive, and Total language scores, and Child Behavior Checklist (CBCL) with Internalizing, Externalizing, and Total behavior scores. Outcome scores of children prenatally exposed to general anesthesia were compared to children without prenatal exposure using multivariable linear regression models adjusting for demographic and clinical covariates (sex, race, income, and maternal education, alcohol or tobacco use, and clinical diagnoses: diabetes, epilepsy, hypertension, psychiatric disorders, or thyroid dysfunction). Bonferroni adjustment was used for the 6 independent tests in the primary analysis, so a corrected P value <.0083 ( P = .05 divided by 6 tests, or a 99.17% confidence interval [CI]) was required for statistical significance. RESULTS: Among 2024 children with available outcome scores, 22 (1.1%) were prenatally exposed to general anesthesia. Prenatally exposed children had higher CBCL Externalizing behavioral scores (score difference of 6.1 [99.17% CI, 0.2-12.0]; P = .006) than unexposed children. Of 6 tests including 11 scores and subscores, only CBCL Externalizing behavioral scores remained significant after multiple comparisons adjustment with no significant differences found in any other score. CONCLUSIONS: Prenatal exposure to general anesthetics is associated with increased externalizing behavioral problems in childhood. However, given the limitations of this study and that avoiding necessary surgery during pregnancy can have significant detrimental effects on the mother and the child, further studies are needed before changes to clinical practice are made.